Current iodine nutrition status and progress toward elimination of iodine deficiency disorders in Jazan, Saudi Arabia - Alsanosy Rashad Mohammed; Gaffar Abdelrahim; Khalafalla Husam Eldin; Mahfouz Mohamed; Zaid Abdel Naser; Bani Ibrahim (BMC, 2012)
Abstract Background The term iodine deficiency disorders (IDD) refers to all the effects of iodine deficiency on growth and development in human and animal populations that can be prevented by correction of the iodine deficiency. The objective of this paper was to determine the iodine nutrition status among schoolchildren in the Jazan Region of the Kingdom of Saudi Arabia (KSA), by measuring urinary iodine concentrations and by clinical assessments of goiter rate. Methods A school-based cross-sectional survey was conducted in the Jazan region of southwestern KSA from May to November 2010. A total of 311 children, aged 6-13 years, drawn from 12 schools, were selected by a three-stage cluster random sampling method. Data on sociodemographic characteristics were collected using a structured questionnaire. Urine samples were collected and physical examinations were conducted to determine the presence or absence of goiter. Data were analyzed using SPSS version 17.0. Chi square and independent t-tests were used for proportions and mean comparisons between groups. Results Out of 360 selected children, 311 were examined. There were 131 males (42%) and 180 females (58%). The median urinary iodine concentration (UIC) of the study group was 421 μg/L. The study population proportion with UIC > 300 μg/L was 74% with a higher proportion among males and urban populations. The proportion of children with UIC of 100-300 μg/L was only 21% and was significantly higher among females compared with males (p < 0.001). Only about 3% of the children had a median UIC less than 50 μg/L. The prevalence of total goiter rate (TGR) among the sample of schoolchildren in Jazan was 11%, with significant variations between rural and urban populations and by gender. Conclusions The present study demonstrates a remarkable achievement in Universal Salt Iodization (USI) and IDD elimination goals in the Jazan area. However, UIC levels reflect excessive iodine intake and may put the population at risk of adverse health consequences like iodine-induced hyperthyroidism and autoimmune thyroid diseases.